THE INFLUENCE OF FOREIGN WORDS ON MODERN RUSSIAN - Chernova T.A.; Abdinazarov Shoxrux Ismoil o’g’li; Khabibullayev Ramadan Botir oglu; Khabibullayev Ramadan Botir oglu (International Journal of Formal Education, 2025)
This article analyzes the influence of words borrowed from foreign languages on the modern Russian language. The reasons for the introduction of words, areas of active use and the attitude of society to such vocabulary are considered. Especially the most common group, English words (Anglicisms), is studied separately. The article emphasizes the need to preserve the culture and uniqueness of the language through the rational use of foreign words.